Hubungan Stres dengan Kualitas Tidur pada Mahasiswa/i Fakultas Kedokteran Universitas HKBP Nommensen - Sitepu, Jenny Novina; Hutahaean, Reinata Gracia; Jirwanto, Hendra (Universitas HKBP Nommensen, 2022)
Introduction: Medical faculty students have a heavy educational burden because they are required to have the ability to take lessons in order to produce qualified doctors. The competency- based curriculum (CBC) used at the Faculty of Medicine increases the educational load of medical students because there is a compaction of assignments and lecture schedules. This makes them even more stressed and spends their time studying late at night which has a negative impact on health and sleep quality. This study aims to determine the relationship between stress and sleep quality in students of the Faculty of Medicine, University of HKBP Nommensen. Methods: The research sample was 97 FK UHKBPN students in the undergraduate medical stage who met the criteria. Data were collected by giving the Depression Anxiety Stress Scale (DASS 42) questionnaire to assess stress and the Pittsburgh Sleep Quality Index (PSQI) questionnaire to assess sleep quality. The relationship between stress and sleep quality was analyzed using Fisher exact test. Results: The results of this study showed that out of 97 respondents, most of them did not experience stress (80.4%) and most had poor sleep quality (84.5%). The results of univariate analysis showed that in 2019’s and 2020’s class, had the highest stress and the worst quality of sleep. The results of the Fisher exact test showed a significant relationship between stress and sleep quality (p = 0.037). Conclusion: There is a significant relationship between stress and sleep quality in students of the Faculty of Medicine, University of HKBP Nommensen Keywords: Stress, Medical Students, Sleep Quality